Multiple signalling options for prostacyclin - Wise Helen (Acta Pharmacologica Sinica, 2016)
The fate of a cell following stimulation by the prostanoid prostacyclin is cell specific, depending not only on the ability of prostacyclin to activate the cell surface prostacyclin (IP) receptor and regulate its coupling to various G proteins, but also on its ability to act intracellularly via the nuclear peroxisome proliferator-activated receptor family (PPAR). This review will highlight the different signalling options available to prostacyclin, and discuss the consequences for cell responses.